Healing plants of Nigeria ethnomedicine and therapeutic applications - Adodo, Anselm; Iwu, Maurice M. (Boca Raton : CRC Press LLC, 2020)
Healing Plants of Nigeria: Ethnomedicine and Therapeutic Applications offers comprehensive information on the use of herbal medicines in West Africa. Combining an evidence-based, ethnobotanical perspective with a pharmacological and pharmaceutical approach to phytomedicine, the book bridges the gap between the study of herbal plants' pharmacological properties and active compounds for the development of clinical drugs and community-oriented approaches, emphasising local use. It demonstrates how the framework of African traditional medicine can be preserved in a contemporary clinical context. The book outlines the history and beliefs surrounding the traditional use of herbs by the local population alongside their application in contemporary phytotherapy in Nigeria and West Africa. It features a critical assessment of the scientific rationale behind the use of these plants in ethnomedicine and offers a composite catalogue of phytotherapeutic and wellness agents, detailing the safety profile, efficacy, and scientific integrity of plants used to treat diseases and optimise health. Features: An ethnobotanical survey containing over 200 full-colour photographs of Nigerian and West African plants. A unique combination of ethnobotany and pharmacognosy, bridging the divide between pharmaceutical and community-oriented approaches to herbal medicine research. Contextual discussion of the therapeutic potential of Nigerian herbal medicine. Offers a template which can be used to separate the superstitious aspects of ethnomedicine from culturally inherited deposits of knowledge. A handbook for herbal and natural medicine practitioners, the book is aimed at African thinkers, scientists, healthcare providers and students of pharmacology and ethnomedicine.
OCLC-licensed vendor bibliographic record.
Keywords: Herbs -- Therapeutic use -- Nigeria; Traditional medicine -- Nigeria; Medicinal plants -- Nigeria; MEDICAL / Pharmacology; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / Evolution